Die regsposisie van kerke in ’n verenigingsproses: die NG Kerk teen die agtergrond van ontwikkelinge in België - Strauss, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
In Belgium three lines of approach by the civic courts of the church developed since the country’s independence in 1831. In the first two lines of approach the autonomy of the assemblies or tribunals of the church – to do things in a just way – is respected and treated as such. The third option remains a possibility but it means that courts may also apply the European Charter of Human Rights as an approach to meet out justice in church affairs.